Selling access, obscuring risk: the discursive construction of financial inclusion in Indonesian digital lending platforms - Joko Santoso (Indonesian Journal of Language and Economic Discourse, 2026)
Background: Digital lending has expanded financial access in Indonesia, yet platform communication may foreground convenience and empowerment while dispersing consequential information about costs, default, data use, and repayment obligations across less visible textual layers. Objective: This study examines how Indonesian digital-lending platforms discursively construct financial inclusion, organise risk visibility, and allocate responsibility among borrowers, lenders, platforms, and regulators. Method: Using a qualitative comparative discourse design, this study analyses 24 primary documents from six licensed platforms, supported by regulatory and industry materials, through an Access-Framing and Legitimation Matrix, a Risk-Visibility and Disclosure-Hierarchy Audit, and an Agency, Responsibility, and Regulatory Legitimation Scheme. Results: Findings show that access is predominantly framed through financial attractiveness, enterprise opportunity, procedural simplicity, flexibility, speed, and regulatory assurance. Risk information is formally present but unevenly distributed, with numerical costs concentrated in FAQs, terms, and deeper product pages, while broader legal, liquidity, and data-related risks remain comparatively limited. Implication: Responsibility is frequently individualised through literacy, affordability assessment, contractual compliance, repayment discipline, and risk acceptance, whereas platforms are represented primarily as enabling and trustworthy infrastructures. Novelty: This study contributes an integrated framework that treats financial inclusion as a discursive architecture linking access, disclosure hierarchy, responsibilisation, and regulatory legitimation rather than as service availability alone in practice